Intimately-coordinated carbon nitride-metal sulfide with high π-d conjugation for efficient battery performance. (December 2021) - Lee, Jang Mee; Selvarajan, Premkumar; Kim, Sungho; Singh, Gurwinder; Joseph, Stalin; Yang, Jae-Hun; Yi, Jiabao; Vinu, Ajayan
Abstract: In this investigation, a hybrid of metal sulfide and carbon nitride (CN) is synthesized by in-situ chemical conversion between metallic species and a single precursor of carbon, nitrogen and sulfur elements through a strong π-d conjugation approach. It is observed that the local chemical alteration in the vicinity of N atom in the CN template triggers the formation of a highly π-conjugated CN system and efficient π-d hybridization at heterointerface. This is accelerated by partial substitution of the Fe atom for Mn ions in the MnS phase which significantly enhances the battery performance, delivering 2031 mA h g −1 after 500 cycles with inverse capacity growth. Via systematic in-depth characterizations, it is found that the gradual increase of Li-ion diffusion coefficients and charge transfer kinetics for repeated cycling is ascribed to the highly dispersed and uniform particles that are confined within the CN template through a strong π-d hybridization. Graphical Abstract: ga1 Highlights: Hybrid of metal sulfide and carbon nitride with high π-d conjugation is prepared. The optimized material shows 2031 mA h g −1 at 1 A g −1 with inverse capacity growth. Significant enhancement in electrochemical dynamics is observed during cycling. With cycling, particle size become confined into 1–3 nm with uniform distribution. Carbon nitride acts as efficient matrix based on strong π-d hybridization.